KEMITRAAN DALAM IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SMA AL-AZHAR KELAPA GADING JAKARTA UTARA - Rizqi Pratama Satria; Supadi Supadi; Winda Dewi Listyasari (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
ABSTRACT The research entitled Partnership in Implementation of School Based Management at SMA Al-Azhar Kelapa Gading aims to identify and obtain an overview of the Partnership Planning, the Partnership Implementation, and the Partnership Monitoring and Evaluation. The research was conducted from November 2016 to July 2017 using a qualitative approach within description method. Data were collected through interviews, observation, and documentation studies. Data analysis was performed through the stages of data reduction, data display, and verification. Investigation and checking the validity of data was performed through the stages of data credibility, transferability, dependability and confirmability. The results of research discussions in partnership planning can be done based on needs analysis, then analyzing the partnership to know potential partners, proposal discussion, negotiation and signing of MoU. In carrying out the partnership to pay attention to the matter of conformity, which means that the partner must have the criteria in accordance with the characteristics of SMA Al-Azhar Kelapa Gading based on religious and partnership programs conducted between the two sides in accordance with the needs of the school. In monitoring and evaluation, there are several strategies that are to conduct direct monitoring during the partnership program and to evaluate both orally and in writing to analyze the weaknesses and lack of partnership program so that in the future monitoring and evaluation result can be an input for future partnership program can be more effective . Advice can be given for this research should be able to maintain the continuity of the course of the partnership as a factor supporting school-based management. Keywords : Partnership, School Based Management